Neurovisual and neurophysiological assessment of the brain in newborn children with perinatal brain damages - P. L. Sokolov; O. V. Klimchuk; N. V. Lapshina; N. S. Tomilina (Acta Biomedica Scientifica, 2018)
Now in practice, the evaluation of the brain condition of a child with perinatal lesions is carried out mainly on the basis of available symptoms and laboratory test data. From hardware diagnostic techniques only neurovisualization is used - MR1, CT and neurosonography. Simple and informative neurophysiological tests, despite the long history of their use, are not used often enough. To objectify the state of neuronal and conducting brain structures, magnetic resonance imaging and the study of auditory brainstem response (ABR) were carried out. The study group consisted of 29 newborn children (10 boys and 19 girls) with perinatal brain lesions. 1n all cases, changes in the structure of the brain tissue on MRI indicate changes in the characteristics of the evoked potential. With signs of damage to myelinated formations, a significant increase in the time parameters of the ABR was noted only in isolated cases (in four children). In 25 cases, the amplitude parameters and the configuration of ABR were varied. Thus, the use of latencies of ABR components as the main source of information for children in the first months of life is inadvisable. The most informative and correlating with the data of MR1 studies are such parameters as the total amplitude level and the splitting of ABR components.